Expressing that you Care for people through Generative AI - Lakshmi Namratha Vempaty (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Caring for People and the Significance of Workplace Positivity. In the contemporary landscape of work, the significance of caring for people and fostering workplace positivity has gained paramount importance. This abstract explores the intertwined concepts of nurturing employee well-being and cultivating a positive work environment. It delves into the multifaceted benefits of prioritizing care and positivity within the workplace, both for individuals and organizations